Hypertension Self-Care Behavior and Its Associated Factors among Patients with Hypertension - Akhmad Azmiardi; Aris widiyanto; Joko Tri Atmojo; Hakim Anasulfalah; Ahmad Syauqi Mubarok; Sri Iswahyuni (Masters Program in Public Health, Sebelas Maret University, 2023)
Background: Hypertension is a chronic medical condition that affects millions of people worldwide and can lead to severe health complications. Hypertension self-care behavior is important in managing their condition and reducing their risk of complication. This study aimed to to determine factors that associated with self-care behavior among patients with hypertension. Subjects and Method: This was cross-sectional study, conducted at Boyolali Regency, Central Java. A total of 122 participant are included in this study. The Independent variables were including age, sex, education level, income, and duration of hypertension. The dependent variable was Hypertension self-care behavior. The data of Hypertension self-care behavior were collected by Hypertension self-care behavior questionnaire (HSCBQ). Knowledge about hypertension was measured using a modified questionnaire of hypertension evaluation of lifestyle and management (HELM). The data were analyzed by multiple logistic regression. Results: Age ≥ 50 years (aOR=3.76; 95%CI=1.30 to 10.50; p=0.014), higher level of education (aOR=6.06; 95%CI=1.91 to 22.85; p=0.003) higher income (aOR=2.89; 95%CI=1.07 to 7.80; p=0.035), longer duration of hypertension (aOR=3.35; 95%CI=1.13 to 9.93; p=0.029) and good knowledge of hypertension (aOR=10.56; 95%CI=3.51 to 31.71; p<0.001) were associated and statistically significant with Hypertension self-care behavior. Conclusion: Older age, higher level of education, higher income, longer duration of hypertension and good knowledge had statistically significant association with good Hypertension self-care behavior. Keywords: age, duration of hypertension, hypertension self-care behavior, income, knowledge, level of education. Correspondence: Akhmad Azmiardi. School of Health Science Mamba’ul ‘Ulum Surakarta. Jln. Ringroad, Mojosongo, Jebres, Surakarta, Central Java, Indonesia. Email: aazmiardi@gmail.com. Mobile: +6285245412021.